Hubungan Kebiasaan Belajar dengan Hasil Belajar Siswa Mata Pelajaran Kimia pada Masa Pandemi Covid-19 - Nur Hijriyati; Rini Muharini; Maria Ulfah; Erlina Erlina; Ira Lestari (Universitas Pendidikan Mandalika Mataram, 2022)
The change in the learning system due to the Covid-19 outbreak has caused changes in student study habits. In the learning process, it was found that students have bad study habits. Good study habits affect learning outcomes. This study aims to describe study habits and learning outcomes and to determine the relationship between study habits and learning outcomes in chemistry subjects. This research was quantitative research with the type of correlation. The research subjects were students ofXII IPA MAN 1 Pontianak. The Instrument used was study habits questionnaire. The correlation testwas analyzed using rankspearman test. The result of the research indicated that study habits and learning outcomes had fairly good category, and there was strong, positive and significant relationship between study habits and learning outcomes with correlation coefficient value of 0,66. Interestingly, female students demonstrated stronger relationship on study habits and learning outcomes than male students. Study habits influence learning outcomes by 44, 35 %.